2020
DOI: 10.3389/fonc.2020.00168
|View full text |Cite
|
Sign up to set email alerts
|

Association of MSH2 Expression With Tumor Mutational Burden and the Immune Microenvironment in Lung Adenocarcinoma

Abstract: Immune checkpoint blockade (ICB) therapies that target programmed cell death 1 (PD1) and PD1 ligand 1 (PDL1) have demonstrated promising benefits in lung adenocarcinoma (LUAD), and tumor mutational burden (TMB) is the most robust biomarker associated with the efficacy of PD-1-PD-L1 axis blockade in LUAD, but the assessment of TMB by whole-exome sequencing (WES) is rather expensive and time-consuming. Although targeted panel sequencing has been developed and approved by the US Food and Drug Administration (FDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Existing evidence showed that MSH2 is overexpressed in pancreatic cancer cells and can be used as a CD4+ helper T cell antigens for the immunotherapy of patients with pancreatic cancer [ 33 ]. In LUAD, high expression of MSH2 was significantly correlated with CD8+ T cell infiltration [ 34 ]. In addition, the loss of MMR protein expression was related to the selective downregulation of human leukocyte antigen class I antigens, which contributes to the immune escape of endometrial carcinomas [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence showed that MSH2 is overexpressed in pancreatic cancer cells and can be used as a CD4+ helper T cell antigens for the immunotherapy of patients with pancreatic cancer [ 33 ]. In LUAD, high expression of MSH2 was significantly correlated with CD8+ T cell infiltration [ 34 ]. In addition, the loss of MMR protein expression was related to the selective downregulation of human leukocyte antigen class I antigens, which contributes to the immune escape of endometrial carcinomas [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMB is a promising biomarker for pan-cancer prediction, leading immunotherapy into the era of precision medicine [ 36 ]. In LUAD, the increase in MSH2 expression was significantly positively correlated with TMB [ 34 ]. Studies have shown that high nonsynonymous TMB was a good prognostic factor for patients with non-small-cell lung cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations lead to a change in amino aicds which may increase the number of neo-antigens theoretically, which could activate the immune system and strengthen the immune cell in ltration. The change in immune microenvironment could affect immunotherapy response and have an impact of prognosis in patients with different cancers [25][26][27][28] . Based on these, TMB is becoming a hot biomarker for various cancers [29][30][31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, to evaluate the prognostic value of risk score, we drew the ROC curve at 5 years of OS and calculated the AUC value. From Supplementary Figure 1B, the 5 year AUC was 0.672 (AUC > 0.65), which revealed superior predictive accuracy in OS (19). Second, for the individual genes, the correlations between their expression levels and prognosis are shown in Figure 6.…”
Section: Risk Score and Survival Analysismentioning
confidence: 91%